2022
DOI: 10.3389/fsurg.2022.1013918
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal natural orifice endoscopic surgery for myomectomy: Can it be a conventional surgery?

Abstract: IntroductionAs a new minimally invasive surgery, transvaginal natural orifice transluminal endoscopic surgery (vNOTES) has been proved to be suitable for the treatment of a variety of gynecological benign diseases. However, compared with other minimally invasive surgeries that have been widely used, such as conventional multiport laparoscopy and transumbilical laparoendoscopic single-site surgery (LESS), their advantages and disadvantages and how to choose are still unknown. The purpose of our study is to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…There was no significant difference in bleeding, duration of surgery, or drop in Hb or Hct between the two groups. The durations of surgery were slightly longer for the vNOTES group than the LESS group, which were consistent with the research of Hou et al [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There was no significant difference in bleeding, duration of surgery, or drop in Hb or Hct between the two groups. The durations of surgery were slightly longer for the vNOTES group than the LESS group, which were consistent with the research of Hou et al [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, 36 vNOTES patients (87.8%) and 84 LESS patients (63.2%) had an event of anal exhaust within 12 h after the operation, which are significantly different ( p = 0.002). Anal-exhaust time is an important observation index for early postoperative intestinal function recovery [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, vNOTES, bene ting from its closer proximity to the target organ and the greater expansibility of the vaginal route compared to the umbilical route, can largely offset the disadvantages of LESS [10]. Moreover, as demonstrated in our previous study [11], vNOTES uterine broid resection can be performed as a routine procedure. Furthermore, in this study, we were delighted to nd that the prone position for broid resection resulted in shorter surgical times compared to the bladder ap position.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have shown that transvaginal vault incision is a traditional surgical approach that provides safe access to the abdominal cavity, with a complication rate of only 1.3% [20]. In our previous research involving 2000 cases of vNOTES procedures, the incidence of visceral injury was as low as 0.4% [21]. Therefore, vNOTES can be routinely performed in gynecological surgeries and aligns with the principles of ERAS.…”
Section: Discussionmentioning
confidence: 91%
“…The vNOTES and TU-LESS procedures performed and the equipment applied in the present study will be similar to those described in previous publications. [24,33,41,42] Recruitment procedures and follow-up plan Recruitment: The enrolment owchart and follow-up plan for the CLOCKBEGIN study are shown in Fig. 1.…”
Section: Study Interventionsmentioning
confidence: 99%